Измеримые многозначные отображения и их селекторы в динамических играх преследования - Чикрий, А.А.; Раппопорт, И.С. (Проблемы управления и информатики, 2006)
Викладено загальний метод розв’язування квазілінійних ігрових задач переслідування. Він базується на методі розв’язувальних функцій. Запропонована схема охоплює широке коло конфліктнокерованих функціональнодиферен- ціальних систем. Аналіз різних форм розв’язувальних функцій дозволяє з’ясувати необхідну інформованість для завершення гри. This paper outlines a general approach to solution of the quasilinear game problems of pursuit. This approach essentially employs the apparatus of the theory of multivalued mappings and is based on the method of resolving functions. Suggested scheme encompasses a wide range of functionaldifferential conflictcontrolled systems. The analysis of various forms of resolving functions allows to clarify what kind of information is necessary for successful termination of the game under study.